Selenium- and tellurium-substituted cyclopropenones and their facile ring-opening with methanol - Werz, Daniel B.; Gleiter, Rolf; Rominger, Frank (European journal of organic chemistry, 2003)
Treatment of donor-substituted acetylenes (X−C≡C−X, with X = R−Se, R−Te) with sodium trichloroacetate, followed by hydrolysis, yielded the corresponding cyclopropenones. Their structures could be elucidated by X-ray analysis, and indicated significant overlap between the p-type lone pairs on the chalcogen atoms and the cyclopropenone unit. DFT calculations were carried out on various conformers in order to clarify their relative energy profiles. Methanolysis of these ring systems at room temperature quantitatively afforded α,β-unsaturated esters. (© Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2003)
First published: 05 December 2002
Gesehen am 27.10.2020